Acute Myeloid Leukemia: From Biology to Clinical Practices Through Development and Pre-Clinical Therapeutics - Roussel, Xavier; Daguindau, Etienne; Berceanu, Ana; Desbrosses, Yohan; Warda, Walid; Neto da Rocha, Mathieu; Trad, Rim; Deconinck, Eric; Deschamps, Marina; Ferrand, Christophe (Frontiers in Oncology, 2020)
Recent studies have provided several insights into acute myeloid leukemia. Studies based on molecular biology have identified eight functional mutations involved in leukemogenesis, including driver and passenger mutations. Insight into Leukemia stem cells (LSCs) and assessment of cell surface markers have enabled individualization of LSCs from hematopoietic stem and progenitor cells. Clonal evolution has been described as having an effect similar to that of microenvironment alterations. Such biological findings have enabled the development of new targeted drugs, including drug inhibitors and blockading of monoclonal antibodies. Some recently approved targeted drugs have resulted in new therapeutic strategies that enhance standard intensive chemotherapy regimens as well as supportive care regimens. Besides the progress made in adoptive immunotherapy, since allogenic hematopoietic stem cell transplantation enabled the development of new T-cell transfer therapies, such as chimeric antigen receptor T-cell and transgenic TCR T-cell engineering, new promising strategies are being investigated.